2015
DOI: 10.1016/j.neurobiolaging.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Breadth and age-dependency of relations between cortical thickness and cognition

Abstract: Recent advances in neuroimaging have identified a large number of neural measures that could be involved in age-related declines in cognitive functioning. A popular method of investigating neural-cognition relations has been to determine the brain regions in which a particular neural measure is associated with the level of specific cognitive measures. Although this procedure has been informative, it ignores the strong interrelations that typically exist among the measures in each modality. An alternative appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 57 publications
7
68
0
Order By: Relevance
“…We replicated prior accounts of the significant association of mean thickness and global cognition, and similarly found a lack of a significant association between reference abilities and mean cortical thickness as in our companion paper (Salthouse et al, 2015). In contrast to our companion paper, however, our approach found that cortical thickness patterns preserve reference-ability specific information.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We replicated prior accounts of the significant association of mean thickness and global cognition, and similarly found a lack of a significant association between reference abilities and mean cortical thickness as in our companion paper (Salthouse et al, 2015). In contrast to our companion paper, however, our approach found that cortical thickness patterns preserve reference-ability specific information.…”
Section: Discussionsupporting
confidence: 86%
“…First, our companion paper (Salthouse et al, 2015) conducted a principal-axis factor analysis with a subsequent oblique rotation on 33 mean values of cortical surface ROIs to retain 5 factors. In the current paper there was no such dimensionality reduction up front; we performed a principal component analysis on the data from all vertices and retained all the PCs for the subsequent regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations